Hernández-Pacheco Sanz, Javier. Hegel: Introducción e interpretación. Independently published, 2019, 268 pp. - Cortés Jiménez, José Carlos (THÉMATA. Revista de Filosofía, 2022)
Reseña de Hernández-Pacheco Sanz, Javier. Hegel Introducción e interpretación. Independently published, 2019. 268 pp.